Things not seen - Clements, Andrew, 1949- (New York : Philomel Books, 2002)
When fifteen-year-old Bobby wakes up and finds himself invisible, he and his parents and his new blind friend Alicia try to find out what caused his condition and how to reverse it.
Lexile
Young Hoosier Book Award Nominee 2004-2005.
1 2 6 9 13 18 19 21 25 31 34 35 38
Keywords: Blind -- Fiction; People with disabilities -- Fiction; Science fiction